A new species of Xinpusaurus (Reptilia, Thalattosauria) from the Ladinian (Middle Triassic) of Xingyi, Guizhou, southwestern China. Issue 6 (1st November 2016) - Li, Zhi-Guang; Jiang, Da-Yong; Rieppel, Olivier; Motani, Ryosuke; Tintori, Andrea; Sun, Zuo-Yu; Ji, Cheng
Abstract : SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Li, Z.-G., D.-Y. Jiang, O. Rieppel, R. Motani, A. Tintori, Z.-Y. Sun, and C. Ji. 2016. A new species of Xinpusaurus (Reptilia, Thalattosauria) from the Ladinian (Middle Triassic) of Xingyi, Guizhou, southwestern China. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1218340.